2005
DOI: 10.1097/01.cad.0000180117.93535.cf
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of phosphatidylinositol-3-kinase synergizes with gemcitabine in low-passage tumor cell lines correlating with Bax translocation to the mitochondria

Abstract: Apoptotic pathways, including the phosphatidylinositol-3-kinase (PI3K)/AKT survival pathway, are altered in most cancer cells in relation to their normal counterparts and these differences may present an excellent therapeutic window. To gain insight into the relevance of the PI3K pathway as a target for drug discovery we generated tumor cell lines from different tumor samples that we maintained at low passage. The characterization of these cell lines indicates that all of them have constitutively activated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…LY294002 increases cytotoxicity induced by antimicrotubule agents such as taxanes and vinca alkaloids in glioma, ovarian cancer, oesophageal cancer, sarcoma and lung cancer cells in vitro and in vivo [100][101][102][103]. Wortmannin treatment sensitised cells to paclitaxel, cisplatin, gemcitabine or 5-fl uorouracil [100,104,105], where potentiation of apoptosis caused by wortmannin was associated with inhibition of AKT activation.…”
Section: Therapeutic Combinationsmentioning
confidence: 99%
“…LY294002 increases cytotoxicity induced by antimicrotubule agents such as taxanes and vinca alkaloids in glioma, ovarian cancer, oesophageal cancer, sarcoma and lung cancer cells in vitro and in vivo [100][101][102][103]. Wortmannin treatment sensitised cells to paclitaxel, cisplatin, gemcitabine or 5-fl uorouracil [100,104,105], where potentiation of apoptosis caused by wortmannin was associated with inhibition of AKT activation.…”
Section: Therapeutic Combinationsmentioning
confidence: 99%
“…Here, a collection of human melanoma cell lines generated from different tumor stages and three mouse melanoma lines of the B16 family were used to investigate the susceptibility of melanoma to PI3K pathway inhibition. Currently, the effect of PI3K inhibition on cell proliferation is controversial (12,22,(24)(25)(26)(27); therefore, we first reevaluated the effect of the classic PI3K inhibitors wortmannin and LY294002. When cells were exposed to a single dose of inhibitor for 3 days, wortmannin was ineffective due to its limited stability ( Fig.…”
Section: Dual Pi3k/mtor Inhibitors Block Proliferation Of Melanoma Cellsmentioning
confidence: 99%
“…The PI3K/AKT signaling pathway regulates several transcriptional factors, including the forkhead transcription factor FKHR and nuclear factor-nB, which are involved in cell cycle control and apoptosis (7)(8)(9)(10)(11). The PI3K/AKT pathway has also been reported to regulate multiple downstream signaling effectors relevant to apoptosis, including the Bcl-2 family member Bad, Bax, caspase-9, c-myc, and YAP (12,13). Furthermore, the PI3K/AKT pathway has been shown to inhibit apoptotic processes, although inhibition of PI3K/AKT signaling sensitizes cells to apoptotic stimuli, such as drug treatment or cellular stress (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies suggested that Bax promotes apoptosis through several interdependent mechanisms, including translocation of Bax from the cytoplasm to the mitochondria, Bax conformational changes, and oligomerization of Bax and Bak (13,(16)(17)(18). Bax expression is closely related to cellular sensitivity to apoptosis.…”
Section: Introductionmentioning
confidence: 99%